Clinical Profile and Risk Factors for Complication of Type 2 Diabetes Mellitus at the National Referral Hospital, Bhutan: A Descriptive Cross‐Sectional Study - Tshering Norbu; Yeshey Dorjey; Sangay Tshering; Namkha Dorji; Guru Prasad Dhakal (Health Science Reports)
ABSTRACT Background and Aim Globally, diabetes mellitus is a major public health concern affecting 10.5% of the population. Nearly 90% of these people have Type 2 diabetes mellitus (T2DM). In Bhutan, T2DM is prevalent in 5.6% of the population, and around 60% are unaware of their diagnosis of diabetes. There is no baseline information on the rate and the risk factors for complications of diabetes in Bhutan. The study assessed the clinical profile and the risk factors for complications of T2DM at the Jigme Dorji Wangchuk (JDW) National Referral Hospital, Bhutan. Methods A descriptive cross‐sectional study was conducted at the JDW National Referral Hospital, Bhutan, from January to December 2019. Patients with T2DM attending diabetic clinics were included in the study. Demographic variables and metabolic profiles were recorded using a standard pro forma. Descriptive statistics were used to express the results. The association of clinical profiles with the microvascular complication was assessed using multivariate logistic analysis with statistical significance at p < 0.05. Results There were 292 patients with T2DM during the study period. The rate of microvascular complication is around 25% in T2DM. Among the complications, diabetic retinopathy occurred in over 51%, followed by neuropathy (29.7%) and nephropathy (18.9%). Over 1/3rd of patients had a duration of diabetes over 10 years with a mean duration of 6.3 (5.4) years, and around 44% (127/292) of them had poor glycemic control (HbA1C ≥ 7%). The age ≥ 60 years and the duration of diabetes ≥ 10 years were independent risk factors for microvascular complications in T2DM patients. Regular exercise prevents retinopathy (OR 0.4, 95%CI 0.2–0.9, p = 0.026). Conclusion There is a microvascular complication in 1 in 4 of type 2 diabetic patients. Age over 60 years and a duration of diabetes of more than 10 years are independent risk factors for microvascular complications, and regular exercise is preventive for microvascular complications.